Tigers - Marsh, Laura F. (Washington, D.C. : National Geographic, 2012)
An introduction to tigers that describes their physical characteristics, behavior, and more.
2.6
K-3
K-3
Keywords: Tiger -- Juvenile literature; Tiger; Tigers; Readers (Elementary)